Trends in COVID-19 vaccine administration across visit types in a safety net pediatric practice during the first year of authorization - Ryan, Grace W.; Goulding, Melissa; Beeler, Angela L.; Nazarian, Beverly L.; Pbert, Lori; Rosal, Milagros C.; Lemon, Stephenie C. (Frontiers in Pediatrics, 2023)
We explored patterns of COVID-19 vaccination across pediatric visit types using electronic health record data from 7/1/2021 through 7/25/2022 in a pediatric safety-net clinic. We generated frequencies and descriptive statistics for patient demographic and vaccine administration variables. Analyses were stratified into age subgroups of 5-to-11-year-olds and 12- to-17-year-olds. 1,409 children received at least one dose of the COVID-19 vaccine and 2,197 doses were administered in this first year of vaccine delivery. Most vaccines given were first doses in the series (45%), followed by second doses (38%), and then booster doses (17%). First doses tended to be given at well-child (42%) or nurse visits (48%), while second doses were almost entirely given at nurse visits (87%) and booster doses at well-child visits (58%). Efforts to optimize COVID-19 vaccination could leverage clinic workflow systems to provide reminder prompts for vaccination for scheduling future doses and identify strategies to facilitate vaccination at non-well child visits, particularly for booster doses.